Загальні засади гармонізації національного законодавства із законодавством Європейського Союзу - Задніпряна‐Корінна, Мар'яна Юріївна; Корінний, Сергій Олександрович (My University, 2023)
To date, the development of the legal system of Ukraine is conditioned by complex external and internal factors, including the need to revise the legislation system and harmonize the legislation of Ukraine with the legislation system of the European Union, ensure effective legal mechanisms for the protection of human rights and freedoms, guarantees of judicial protection of violated rights and compensation for damages to victims persons acquire priority importance. The legal foundations of the harmonization of Ukrainian legislation with the legislation of the European Union were laid in the 90s of the 20th century. Requirements for the harmonization of Ukrainian legislation with the legislation of the European Union have been enshrined in national legislation since 1996, which is connected with the conclusion of the Interim Agreement between Ukraine and the European Communities on trade and trade cooperation. The use of special methods of harmonization with the aim of bringing Ukrainian legislation to the requirements of the European Union is becoming more and more relevant. The choice of the main method of harmonization is based on the experience of a number of European countries that carried out comprehensive harmonization of legislation before becoming a member of the European Union. Quite often, the term "adaptation" is used as close to harmonization. According to the official documents of Ukraine, adaptation means bringing the laws of Ukraine and other normative legal acts into compliance with the acquis communautaire. Adaptation is an integral part of legal integration, which is interpreted as the adaptation of certain phenomena to the environment, conditions of existence, or can manifest as a change in their form, content under the influence of external or internal factors. harmonization of Ukrainian legislation has positive aspects that contribute to the country's development and strengthening its position in the European arena. For example, integration with European structures. The harmonization of the legislation of Ukraine with the legal norms of the European Union is an important step towards the integration of Ukraine into the European space. This helps to improve cooperation with EU countries, simplifies trade, attracting foreign investments and ensures mutual recognition of the rights and responsibilities of citizens. Harmonization of legislation helps to create a favorable investment climate, improve the quality of legislation and other important factors for the functioning of a modernized society. Harmonization as a special method used for the transformation of legislation, legal norms, principles with the aim of assimilation, establishment of requirements common to the legal system of the European Union to various subjects of legal relations, and used as a tool for implementing national policy in the field of harmonization, is applied by a specially authorized by the central body of executive power (as a rule, the Ministry of Justice). A special authorized body in the field of harmonization is a central-level executive authority whose function is to participate in the development of the harmonization policy (a component of the European integration policy), coordinate the implementation of programs for its implementation, and monitor the results of implementation. The effective use of means of the method of harmonization in the analyzed field should take into account the positive European experience of the implemented reforms

На сьогоднішній день розвиток правової системи України обумовлений складними зовнішніми та внутрішніми чинниками, серед яких фактори необхідності перегляду системи законодавства та гармонізації законодавства України з системою законодавства Європейського Союзу, забезпечення дієвих правових механізмів захисту прав і свобод людини, гарантій судового захисту порушених прав та відшкодування шкоди потерпілим особам набувають пріоритетного значення. Правові засади гармонізації українського законодавства з законодавством Європейського Союзу були закладені у 90-х роках ХХ ст. Вимоги щодо гармонізації українського законодавства з законодавством Європейського Союзу отримали закріплення в національному законодавстві ще з 1996 р., що пов’язано з укладанням Тимчасової угоди між Україною та Європейськими Співтовариствами про торгівлю та торговельне співробітництво. Використання спеціальних методів гармонізації з метою приведення українського законодавства до вимог Європейського Союзу набуває дедалі більшої актуальності. Обрання основним методу гармонізації обґрунтовується досвідом низки європейських країн, що здійснили комплексну гармонізацію законодавства перед набуттям членства в Європейському Союзі. Досить часто термін «адаптація» вживають як близький до гармонізації. Відповідно до офіційних документів України адаптація означає приведення законів України та інших нормативно-правових актів у відповідність до acquis communautaire. Адаптація є складовою частиною правової інтеграції, що трактується як пристосування певних явищ до навколишнього середовища, умов існування або може проявлятись як зміна їх форм, змісту під впливом зовнішніх чи внутрішних чинників. гармонізація законодавства України має позитивні аспектів, які сприяють розвитку країни і зміцненню її позицій в європейській арені. Наприклад, інтеграція з європейськими структурами. Гармонізація законодавства України з правовими нормами Європейського Союзу є важливим кроком у напрямку інтеграції України в європейський простір. Це допомагає покращити співробітництво з країнами ЄС, спрощує торгівлю, залучення іноземних інвестицій та забезпечує взаємне визнання прав та обов’язків громадян. Гармонізація законодавства допомагає створити сприятливий інвестиційний клімат, підвищення якості законодавства та інші важливі чинники для функціонування сучасного модернізованого суспільства. Гармонізація як спеціальний метод, що використовується для трансформації законодавства, правових норм, принципів з метою уподібнення, встановлення спільних з системою законодавства Європейського Союзу вимог до різних суб’єк- тів правовідносин, та використовується як інструмент впровадження загальнодержавної політики в сфері гармонізації, застосовується спеціально уповноваженим центральним органом виконавчої влади (як правило, Міністерством юстиції). Спеціальний уповноважений орган у сфері гармонізації – орган виконавчої влади центрального рівня до функції якого належить взяття участі в розробці політики з гармонізації (складова євроінтеграційної політики), координації реалізації програм на її виконання, проведення моніторингу за результатом виконання. Ефективне використання засобів методу гармонізації в аналізованій сфері має відбуватися з урахуванням позитивного європейського досвіду впроваджуваних реформ
Keywords: кафедра економіки і права; adaptation; harmonization of legislation; approximation; general principles; legislation of the European Union; адаптація; гармонізація законодавства; наближення; загальні принципи; законодавство Європейського Союзу